Tumor Treating Fields Suppression of Ciliogenesis Enhances Temozolomide Toxicity - Shi, Ping; Tian, Jia; Ulm, Brittany S.; Mallinger, Julianne C.; Khoshbouei, Habibeh; Deleyrolle, Loic P.; Sarkisian, Matthew R. (Frontiers in Oncology, 2022)
Tumor Treating Fields (TTFields) are low-intensity, alternating intermediate-frequency (200 kHz) electrical fields that extend survival of glioblastoma patients receiving maintenance temozolomide (TMZ) chemotherapy. How TTFields exert efficacy on cancer over normal cells or interact with TMZ is unclear. Primary cilia are microtubule-based organelles triggered by extracellular ligands, mechanical and electrical field stimulation and are capable of promoting cancer growth and TMZ chemoresistance. We found in both low- and high-grade patient glioma cell lines that TTFields ablated cilia within 24 h. Halting TTFields treatment led to recovered frequencies of elongated cilia. Cilia on normal primary astrocytes, neurons, and multiciliated/ependymal cells were less affected by TTFields. The TTFields-mediated loss of glioma cilia was partially rescued by chloroquine pretreatment, suggesting the effect is in part due to autophagy activation. We also observed death of ciliated cells during TTFields by live imaging. Notably, TMZ and TTFields have opposing effects on glioma ciliogenesis. TMZ-induced stimulation of ciliogenesis in both adherent cells and gliomaspheres was blocked by TTFields. Surprisingly, the inhibitory effects of TTFields and TMZ on tumor cell recurrence are linked to the relative timing of TMZ exposure to TTFields and ARL13B+ cilia. Finally, TTFields disrupted cilia in patient tumors treated ex vivo. Our findings suggest that the efficacy of TTFields may depend on the degree of tumor ciliogenesis and relative timing of TMZ treatment.